The FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN SEKTOR PERTANIAN (Studi Empiris Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Fitri Deasy (Jurnal Akuntansi, 2020)
The purpose of this research is to analyze the factors that influence the capital structure of companies in the agricultural sector listed in Indonesian Stock Exchange. Factors used in this study include : capital structure, asset structure, profitability, free cash flow, liquidity. The population of agricultural sector is 21 companie. Due to data availability only 10 companies are selected as a sample. Using multiple regression method, descriptive analysis and interpreted. The result shows that simultaneously asset structure, profitability, free cash flow, and liquidity have significant effect on the capital structure. Partially, free cash flow and liquidity have significant effect on capital structure, while profitability does not.